Природные воды и здоровье человека - Моисеев, А.Ю. (Геологічний журнал, 2010)
Розглянуто вплив природних вод на здоров'я населення і визначено перспективи подальших досліджень у даній області. Особливу увагу приділено проблемам практичного застосування природних мінеральних вод з підвищеним вмістом біологічно активних мікрокомпонентів. Influence of natural waters on a human health is considered and is determined the prospects of further researches in this area. The special attention applies on the problems of practical application of natural mineral waters with considerable concentration of bioactive compounds.